Characterisation of the oxide film on the taper interface from retrieved large diameter metal on polymer modular total hip replacements. (September 2015) - Zeng, P.; Rainforth, W.M.; Cook, R.B.
Abstract: Many metal joint failures have been associated with adverse local tissue reactions due to the response of the body to wear debris and corrosion products, released from the bearing surfaces or the taper interfaces. The oxide film on the CoCrMo plays an important role in the electrochemical behaviour, however, there is a lack of quantitative data on the structure and distribution of oxides following in vivo operation. In the present study, detailed analysis of the surface layer on the taper interfaces is provided. Two retrieved taper interfaces were analysed. Site-specific FIB/TEM cross-sections show evidence of the oxide film and the carbonaceous layer. High resolution TEM results show the oxide film has porous texture and EELS confirmed it is chromium oxide. Highlights: Two retrieved taper interfaces were analysed using advanced electron microscopies. An amorphous carbonaceous layer was observed, EEL spectra often exhibit a π⁎ peak. An oxide film with an amorphous and porous structure was seen, which is Cr oxide. A nanocrystalline layer was seen at the outer surface of the metal in all areas.